Comparative study of cogeneration systems in a chemical industry - Costa, MHA; Balestieri, José Antônio Perrella [UNESP] (Elsevier B.V., 2001)
With the large penetration of the natural gas into the Brazilian energy structure, industries such as paper mills and chemical plants are analyzing the feasibility of implementing cogeneration schemes appropriate to this fuel. The analysis of the energy demand patterns of a chemical company from the photographic sector revealed the possibility of using combined cycles or diesel engine cogeneration schemes keeping the existing compression refrigeration units and steam or gas cycle cogeneration systems with absorption refrigeration units. In terms of economic attractiveness, an analysis based on the method of the internal rate of return was performed. The results indicated that the schemes composed by reciprocating engines and combined cycle with compression chillers, as well as the gas cycle scheme with absorption chiller, present return periods of up to 3 years, showing that the investment in cogeneration could be of interest for this plant. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: cogeneration; feasibility study; natural gas